HR Development And Compensation Development Strategy On The Satisfaction Of Work And Its Impact On Employee Performance - Nova Mardiana; Andi Desfiandi; Ardanta Istari (Proceeding International Conference on Information Technology and Business, 2017)
Based on the performance measurement, the 2016 Performance Indicator agreed between the Director General of Health Efforts Development of Ministry of Health and the President Director of Abdul Moeloek Hospital has not fully achieved the set target. The authors suspect that the target is not achieved is due to lack of performance and employee job satisfaction. This is the impact of the management of human resource management that is allegedly less targeted, especially in the areas of human resource development and employee compensation is not appropriate. This research is survey with Path analysis. Functional employee of General Hospital. Abdul Moeloek numbered 669 employees. Samples taken by 250 respondents. The conclusion of this research is that the research support the proposed hypothesis, that is (1) there is relationship of human resource development and compensation to the employees, (2) there is influence of human resources development and compensation partially to employee job satisfaction, (3) the influence of human resource development and compensation simultaneously on job satisfaction of employees of RSAM, (4) there is influence of job satisfaction on RSAM employee performance. Suggestion from this research is employee development must be done continuously according to employee requirement and compensation in the form of remuneration succeed to improve job satisfaction and employee performance, therefore must be maintained.Keywords: Human Resource Development, Compensation, Job Satisfaction and Employee Performance.